Determination of two kinds of sources simultaneously for a stochastic wave equation. (3rd July 2015) - Yuan, Ganghua
Abstract: In this paper, we derive a Carleman estimate for a stochastic wave equation. Then we apply the Carleman estimate to solve an inverse source problem of determining two kinds of sources simultaneously for a stochastic wave equation. Our main result is a uniqueness result for the inverse source problem.